Shoppersâ Perception On Physical Condition Of Shopping Centersâ Atmosphere At Different Lifecycle - Pribadi Widodo, Astrid Kusumowidagdo, Agus Sachari, (Universitas Prasetiya Mulya, 2012)
Shopping center with atmospheric stimuli design needs to be well formulated in marketing strategy to expose its competitive advantage. As a result, most designs included in the marketing tactic scheme pay more attention to all factors related to the lifestyle in order to make designs exist and be appreciated by the society. Design is one of the key factors of shopping center to gain its success. This research aimed to find out to what extent the visitors perception is different towards shopping centers which has different lifecycles. The research studied two things, first was exploratory research intended to find the embodiment of atmospheric (atmospheric variables).The second research was done in a quantitative method, (multiple regression). This research studied the perception of a hundred mall visitors regarding how the variables of the interior atmosphere affected their shopping habit. The independent variables in the research were the exterior features and building configuration, interior features and supporting facilities. The dependent variable was the the visitor behavior. As a conclusion, the atmospheric interior design of a mall that is embodied in its interior element supported the hypothesis which said that existence of experience which felt differently according to visitor perception at shopping centers in different lifecyle.DOI :Â https://doi.org/10.21632/irjbs.5.2.87-100Keywords: atmospheric stimuli, design features, consumer behavior, shopping center lifecycle